UNFAIR BUSINESS COMPETITION BY PT FORISA NUSAPERSADA AS A MARKET LEADER - Angelene Vivian Gunawan (Kanun Jurnal Ilmu Hukum, 2022)
In the business world, business competition is a natural thing. Business actors conduct business competition to dominate the relevant market or achieve a dominant position. Mastery of a dominant position is allowed as long as it is achieved in one's own capacity and in an equitable manner. To achieve a dominant position in the market, it is not uncommon for business actors to use unjustified methods so that actions from prohibited business competition emerge. The purpose of this study is to determine the regulation of the dominant position in business competition law in Indonesia and to analyze indications of abuse of the dominant position by PT Forisa Nusapersada as containedinKPPU's Decision Number: 14/KPPU-L/2015which continues until the cassation as decided inSupreme Court Decision Number: 1106 K/Pdt.Sus-KPPU/2017.Through this research, it is concluded that the dominant position regulation in business competition law in Indonesia is contained inLaw Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition.In the case of PT Forisa Nusapersada,there are different indications of abuse of the dominant position which have led to different decisions between the KPPU and the Supreme Court.